DNA content analysis of colorectal cancer defines a distinct ‘microsatellite and chromosome stable’ group but does not predict response to radiotherapy - Fadhil, Wakkas; Kindle, Karin; Jackson, Darryl; Zaitoun, Abed M.; Lane, Nina; Robins, Adrian; Ilyas, Mohammad (Wiley, 2014)
Colorectal cancers (CRC) are thought to have genetic instability in the form of either microsatellite instability (MSI) or chromosomal instability (CIN). Recently, tumours have been described without either MSI or CIN, that is, microsatellite and chromosome stable (MACS) CRCs. We investigated the (i) frequency of the MACS-CRCs and (ii) whether this genotype predicted responsiveness to neoadjuvant chemoradiotherapy. To examine the frequency of MACS-CRCs, DNA content (ploidy) was examined in 89 sporadic microsatellite-stable CRCs using flow cytometry. The tumours were also screened for mutations in KRAS/BRAF/TP53/PIK3CA by QMC-PCR. To examine the value of tumour ploidy in predicting response to chemoradiotherapy, DNA content was tested in a separate group of 62 rectal cancers treated with neoadjuvant chemoradiotherapy. Fifty-one of 89 CRCs (57%) were aneuploid and 38 (43%) were diploid. There was no significant association between mutations in TP53/KRAS/BRAF/PIK3CA and ploidy. Testing of association between mutations revealed only mutual exclusivity of KRAS/BRAF mutation (P < 0.001). Of the 62 rectal cancers treated with neoadjuvant chemoradiotherapy, 22 had responded (Mandard tumour regression grade 1/2) and 40 failed to respond (Grade 3–5). Twenty-five of 62 (40%) tumours were diploid, but there was no association between ploidy and response to therapy. We conclude that MACS-CRCs form a significant proportion of microsatellite-stable CRCs with a mutation profile overlapping that of CRCs with CIN. A diploid genotype does not, however, predict the responsiveness to radiotherapy.